Pengaruh Biaya Produksi dan Penjualan Terhadap Pendapatan Laba Bersih Perusahaan yang Terdaftar di Bursa Efek Indonesia (Studi Kasus Pada PT Unilever Indonesia: Studi Kasus Pada PT Unilever Indonesia - Ayu Niken Faizati; Noorlaily Maulida; Abdul Kadir; Dewi Ariefahnoor (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
One of the factors that causes a company to grow is because of the maximum income or profit obtained. When raw material prices rise or there is an increase in labor and overhead costs , the company must incur higher costs to produce products. If this condition s not balanced with selling price adjustments, the profit margin will narrow and net profit will decrease. Net profit is a key indicator that reflects ai company's financial performance. Profit is a basic and important position of the financial overview that has various uses in various contexts, the definition of profit itself is the difference between expenses and income. The effect of production and sales costs on net profit at PT Unilever Indonesia Tbk during the period 2015 to 2022 reflects the complex phenomena faced by the company in carrying out its operations. During this period, PT Unilever faced various challenges organiting from market conditions, changes in rai material prices, and fluctuating consumer demand. The results of this study indicate that: (1) Production costs partially do not have ai significant effect on net profit, this is evidenced by ai significance value of 0.363 > 0.05. (2) Sales partally have ai significant effect on net profit, this is proven by ai significance value of 0.035 < 0.05. (3) Production and sales costs simultaneously haive ai significant effect on net profit, this is proven by ai significance value of 0.000 < 0.05. (4) The influence of the independent variables of production and sales costs on the dependent variable of net profit is 89.3%, while the remaining 10.7% is influenced by other factors outside this reseairch model.